JOINT CONFERENCE – ACOUSTICS 2018 - JOINT CONFERENCE – ACOUSTICS 2018, Chronicle (Archives of Acoustics, 2018)
The paper contains the abstracts of papers presented during JOINT CONFERENCE – ACOUSTICS 2018: 65th Open Seminar on Acoustics 35th Symposium on Hydroacoustics Polish-German Structured Conference on Acoustics Ustka, Poland, September 11 – 14, 2018